O złości, gniewie i agresji jako strategii radzenia sobie z poczuciem wstydu - Makowska, Sandra (Studia Edukacyjne, 2026)
Shame is a social emotion that can pose a significant challenge for children, particularly in situations that threaten their sense of self-worth, agency, and belonging. In response to such experiences, children often resort to coping strategies characterized by the overt expression of intense emotions, such as anger, rage, and aggression. The aim of the study is to identify and present children’s statements regarding their ways of coping with feelings of shame, which manifest through the open display of aggressive reactions, including self-aggressive behaviors. The methodological framework of the study is grounded in a phenomenographic approach, which allows for capturing the diverse ways in which participants experience and make sense of a given phenomenon. The research material was collected through group interviews conducted with school-aged children. The analysis revealed three distinct strategies for coping with shame: (a) aggression directed at others (motivated by the need for retaliation or overt expression of dissatisfaction), (b) aggression directed at objects (as a means of releasing tension), and (c) self-aggression (as a form of self-punishment for failing to meet one’s own or others’ expectations). The findings indicate that these behaviors serve to protect the child’s identity and help restore a sense of control in social situations. Understanding these mechanisms may support adults in responding appropriately to children’s emotional needs and in fostering constructive ways of coping with shame.